Progress stories and the contested making of minerals in Greenland and northern Québec. (December 2022) - Bjørst, Lill Rastad; Rodon, Thierry
Highlights: Northern communities as co-investors of mining projects Making Minerals in Québec and Greenland PDAC, Québec Mines, Nunavik Mining Event ethnography Progress stories Frontier speak Mining strategies The politics of investment The role of government (and communities) in these narratives of wealth creation Mining histories Abstract: The aim of this article is to go beyond progress stories presented in and about the North by industry and governmental bodies. By pursuing event ethnography and public policy analysis, progress stories are analyzed and contextualized, drawing on recent insights from participant-observations at mining conferences and conventions (e.g. PDAC), field visits (organized by REXSAC and the MinErAL Network) to Greenland and Quebec. Quebec has a long history of mining, and in Greenland substantial profit from mining has also been possible (before the Greenland Self-Government authorities took over the responsibility for the mineral resource area). Northern communities are in many ways co-investors of mining projects and promised to benefit from the extractive activities. However, with a (2014) mining strategy preparing Greenland for something that never really happened. Mining in Greenland is still carried out, but the making of minerals there is contested. Around the same time, Québec launched Plan Nord and initiatives mostly aimed at fostering mining investment and development in Northern Québec. The analysis illustrates that development of the mining industry in praxis is much more modest than envisioned, but still the progress stories do have an impact on local politics, the understanding of history, and relationships between North and South.